The impact of the Driver model on cognitive achievement and learning to perform some basic football skills for students - Al-Jubouri, Asst.prof.Dr. Alaa Hassan Ali; Al-Shammari, L.Dr. Zaid Samsam Turki; Hussein, Asst.L.Muntadhar Ali Abdul (Sulaimani Journal for Humanities, 2026)
The focus on improving and enhancing the educational process has become a primary concern for educational institutions and many researchers. This aims to facilitate the delivery of information to students and develop their skills. Therefore, it is essential to move beyond the teacher's role in information delivery. Modern teaching models are needed, shifting the center of activity in the learning process from the teacher to the student, who is now a key element. This is achieved through a model containing organized, planned, and purposeful steps that the teacher follows to reach their objectives. Accordingly, we need new and modern teaching models to be applied in the field of physical education, such as the Driver model, as it helps motivate students and stimulate their cognitive drive to learn. This research aims to: 1- Identify the impact of the Driver model on the cognitive achievement and learning of some basic football skills among first-year students at the College of Physical Education and Sports Sciences, University of Babylon. 2- Determine the superior impact of the Driver model compared to the teaching method used by the instructor on students' cognitive achievement and learning of some basic football skills. As for the research methodology and field procedures, the researcher used the experimental method with two independent equivalent groups, using a pre-test and post-test, on a sample of (30) first-year students at the College of Physical Education and Sports Sciences, University of Babylon. The sample was divided into two groups of (15) students each: the experimental group, which studied the Driver model, and the control group, which studied using the method employed by the course instructor.